Eco-friendly functional polymers : an approach from application-targeted green chemistry /: an approach from application-targeted green chemistry. (2021) - Palencia, Manuel; Lerma, Tulio A; Garcés, Viviana; Mora, Mayra A; Martínez, Jina M; Palencia, Sixta L
No abstract available